2007
DOI: 10.1021/bm070001k
|View full text |Cite
|
Sign up to set email alerts
|

Designed Chain Architecture for Enhanced Migration Resistance and Property Preservation in Poly(vinyl chloride)/Polyester Blends

Abstract: Blends of poly(vinyl chloride) (PVC) and poly(butylene adipate) (PBA) with varying degrees of branching were analyzed with respect to migration resistance during aging in water, preservation of material properties, and thermal stability. Gas chromatography-mass spectrometry, water absorption, weight loss, thermogravimetric analysis, Fourier transform infrared spectroscopy, contact angle, tensile testing, and differential scanning calorimetry were used to analyze the blends before and after aging in water for 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…Plasticizer migration resistance could also be improved when branched plasticizers were used [18,28,29,30]. It has been shown that blending PBSA into PLA could facilitate crystallization of PLA and mitigate the brittleness of PLA when the phase separation could be reduced by adding compatibilizer or annealing the blends [20,27].…”
Section: Introductionmentioning
confidence: 99%
“…Plasticizer migration resistance could also be improved when branched plasticizers were used [18,28,29,30]. It has been shown that blending PBSA into PLA could facilitate crystallization of PLA and mitigate the brittleness of PLA when the phase separation could be reduced by adding compatibilizer or annealing the blends [20,27].…”
Section: Introductionmentioning
confidence: 99%
“…Highly branched PBA was not a good alternative as a PVC plasticizer because of rather poor miscibility and higher hydrophilicity. 11 However, slightly branched PBA exhibited better plasticizing efficiency and migration resistance compared to the linear and highly branched ones. 12,13 Polycaprolactones and their copolymers have also been considered as alternatives to phthalate plasticizers.…”
Section: Introductionmentioning
confidence: 97%
“…Lindström and Hakkarainen10 designed improved PBA plasticizers, by introducing different degrees of branching and different end groups. Highly branched PBA was not a good alternative as a PVC plasticizer because of rather poor miscibility and higher hydrophilicity 11. However, slightly branched PBA exhibited better plasticizing efficiency and migration resistance compared to the linear and highly branched ones 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…The main negative aspect of these plasticizers was their lower efficiency in the processing and plasticization of PVC compared to the low‐molecular‐weight plasticizers; this resulted in a higher tensile strength and stiffness and a lower elongation at break for P‐PVC. Also, there was a possibility of the degradation of these polymeric plasticizers in working media, so this issue must be considered …”
Section: Introductionmentioning
confidence: 99%